Tracing the Itinerant Path. Jishu Nuns of Medieval Japan, by Caitilin J. Griffiths. - Phillips, Nathalie (Buddhist Studies Review, 2018)
Tracing the Itinerant Path. Jishu Nuns of Medieval Japan, by Caitilin J. Griffiths. University of Hawai’i Press, 2016. 214pp., Hb. £68.95 ($65.00). ISBN-13: 9780824859367.